Development of large size crystal growth technology of oxide eutectic scintillator and a proto-type Talbot–Lau imaging system. (29th January 2021) - Kamada, Kei; Yamaguchi, Hiroaki; Yasui, Nobuhiro; Ohashi, Ryota; Den, Toru; Kim, Kyoung Jin; Yoshino, Masao; Yamaji, Akihiro; Kurosawa, Shunsuke; Shoji, Yasuhiro; Yokota, Yuui; Kochurikhin, Vladimir. V.; et al.
Abstract: Wafers of Tb-doped GdAlO3 / α -Al2 O3 eutectic were fabricated by the micro-pulling-down method using an Ir crucible with a 25 × 25 mm 2 die. A prototype X-ray phase imaging detector was developed using a CMOS sensor with a fiber optic plate and the eutectic wafer. X-ray spots with an 8.24  μ m period were observed using the detector. X-ray phase imaging of a nylon ball with a diameter of 4 mm was also carried out. It was observed that a phase change of approximately 2  μ m occurs at the air–nylon interface. This technique of X-ray phase imaging can be realized in the absence of an absorption grating.